2020
DOI: 10.3847/2041-8213/ab86b8
|View full text |Cite
|
Sign up to set email alerts
|

Solar Disk Center Shows Scattering Polarization in the Sr i 4607 Å Line

Abstract: Magnetic fields in turbulent, convective high-β plasma naturally develop highly tangled and complex topologies-the solar photosphere being the paradigmatic example. These fields are mostly undetectable by standard diagnostic techniques with finite spatio-temporal resolution due to cancellations of Zeeman polarization signals. Observations of resonance scattering polarization have been considered to overcome these problems. But up to now, observations of scattering polarization lack the necessary combination of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 51 publications
(102 reference statements)
2
20
0
Order By: Relevance
“…Motivated by the theoretical investigation of Trujillo Bueno & Shchukina (2007), observations with the Zürich Imaging Polarimeter (ZIMPOL) have been carried out at the GREGOR telescope of the Observatorio del Teide (Tenerife; Spain) to study the spatial variability of the polarization signals at different distances from the solar limb (Bianda et al 2018;Dhara et al 2019), finding variations at granular scales for all the observed heliocentric angles. More recently, Zeuner et al (2020) used the Fast Solar Polarimeter (FSP 2) attached to the Dunn Solar Telescope of the Sacramento Peak Observatory (USA) and applied a novel strategy to increase the signal to noise ratio of their disk-center filter polarimetric observations in the Sr I 4607 Å line. Although their successful detection of forward scattering polarization confirms the theoretical predictions, a satisfactory confrontation with the recent theoretical results of del Pino requires taking into account the instrumental degradation produced by their specific observational setup.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the theoretical investigation of Trujillo Bueno & Shchukina (2007), observations with the Zürich Imaging Polarimeter (ZIMPOL) have been carried out at the GREGOR telescope of the Observatorio del Teide (Tenerife; Spain) to study the spatial variability of the polarization signals at different distances from the solar limb (Bianda et al 2018;Dhara et al 2019), finding variations at granular scales for all the observed heliocentric angles. More recently, Zeuner et al (2020) used the Fast Solar Polarimeter (FSP 2) attached to the Dunn Solar Telescope of the Sacramento Peak Observatory (USA) and applied a novel strategy to increase the signal to noise ratio of their disk-center filter polarimetric observations in the Sr I 4607 Å line. Although their successful detection of forward scattering polarization confirms the theoretical predictions, a satisfactory confrontation with the recent theoretical results of del Pino requires taking into account the instrumental degradation produced by their specific observational setup.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, Hanle rotation signatures in the Sr i line have once been reported in the review by Bellot Rubio & Orozco Suárez (2019), and are referred to as "not common". These Stokes U signals in Sr i, due to a deterministic magnetic field, should not be confused with Stokes U theoretically predicted (del Pino Alemán et al 2018) and observationally detected (Zeuner et al 2020) at the center of the solar disk, which is predominantly caused by the axial symmetry break of the radiation field due to local inhomogeneities of the photosphere. We recall that the upper limit of magnetic field strengths detectable with the Hanle effect is given by the Hanle saturation (e.g., Trujillo Bueno 2001), which for the Sr i line is about 200 G (del Pino Alemán et al 2018).…”
Section: Introductionmentioning
confidence: 49%
“…Thus, the Zeeman effect induced by solar magnetic fields can also be excluded as a source for the Stokes U/I signals in the Sr i line. The possibility that the Sr i U/I signals are due to horizontal inhomogeneities that break the axial symmetry of the problem (i.e., granulation, like found by Zeuner et al 2020) is ruled out by the long integration time of over an hour. This long integration time implies that the spatio-temporal resolution is too low to resolve granules, which have a lifetime of only several minutes (Hirzberger et al 1999).…”
Section: Discussionmentioning
confidence: 99%

Hanle rotation signatures in Sr I 4607 Å

Zeuner,
Belluzzi,
Guerreiro
et al. 2022
Preprint
Self Cite
“…These results can be reconciled if the hidden magnetic field of the quiet Sun is much stronger in intergranular lanes than in granules, since the radiation emitted by molecules comes mainly from granules (Trujillo Bueno et al 2004;Trujillo Bueno 2003). There is evidence that this is indeed the reality, but detecting Hanle signatures with some spatial resolution is still an observational challenge (Zeuner et al 2020(Zeuner et al , 2018del Pino Alemán et al 2018;Dhara et al 2019). So far, the spatial distribution of the hidden field has not been observed nor its strength firmly inferred.…”
Section: Introductionmentioning
confidence: 99%